Removing vitamin and trace mineral premixes from finisher diets (154 to 247 lb) did not affect growth performance, carcass characteristics, or meat quality - Kim, I.H.; Lee, J.H.; Park, J.S.; Kropf, Donald H.; Johnston, S.L.; Sorrell, P.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Average daily gain; ADFI; F/G; dressing percentage; tenth rib fat thickness and depth; and color, firmness, and marbling of the longissimus muscle were not influenced by omitting the vitamin and(or) trace mineral premixes from diets during finishing (154 to 247 lb). Thus, omitting vitamin and trace mineral premixes can decrease diet costs without decreasing performance or meat quality of high-lean pigs.
Keywords: Swine; Finishing pigs; Vitamins; Minerals; Meat quality; Growth